The modern military leader as sensemaker on the battlefield - Bester, Piet; O'Neil, Johnny (Scientia Militaria - South African Journal of Military Studies, 2022)
The study on which this article reports, addressed the problem with which modern military leaders on the battlefield are faced in assisting the soldier at basic level to make sense of what is happening. In this study, the term ‘sensemaker’ implied a process of individual and group sensemaking that forms the basis for meaning-making in the volatile, unpredictable, complex and ambiguous (VUCA) world within which soldiers are functioning. The authors postulate a best-fit world view for military leaders in this military leadership sensemaking and meaning-making nexus. They coined ‘social constructivism in complexity’ where the military leader acts as a guide for soldiers through a sensemaking process. This process is graphically represented, and requires a toolkit to assist military leaders in working as sensemakers on the battlefield. The article concludes with recommendations to military psychologists and military educators who have to make policy changes to develop and implement such a toolkit for sensemaking on the battlefield.